2008
DOI: 10.1254/jphs.fm0070288
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Topics of Bone Metabolism: Antiresorptive Microbial Compounds That Inhibit Osteoclast Differentiation, Function, and Survival

Abstract: Abstract. The mass and function of bones depends on the maintenance of a complicated balance between osteoclast-mediated bone resorption and osteoblast-mediated bone formation. Osteoporosis typically reflects an imbalance in skeletal turnover, such that bone resorption exceeds bone formation. Osteoclasts are target cells for anti-osteoporosis therapies. To discover new types of antiresorptive agents, we screened for natural compounds that regulate osteoclast differentiation, function, and survival. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…It integrates into osteoclasts and kills them. Its inhibitory effect on bone resorption was observed in animal studies [147] as well as in vitro studies [148]. It seems that reveromycin A will be a novel antiresorptive agent in future.…”
Section: Igfsmentioning
confidence: 89%
“…It integrates into osteoclasts and kills them. Its inhibitory effect on bone resorption was observed in animal studies [147] as well as in vitro studies [148]. It seems that reveromycin A will be a novel antiresorptive agent in future.…”
Section: Igfsmentioning
confidence: 89%
“…Statins are known to upregulate BMP‐2 expression (Mundy et al, ) and promote osteoblast differentiation and mineralization (Maeda et al, ). In addition, it has been reported that statins also inhibit the formation and activity of osteoclasts (Hughes et al, ; Jeon et al, ; Woo et al, ) by reducing the expression of the osteoclastic enzyme cathepsin K. Thus, statins play an important role in both osteoblast activation and osteoclast inhibition, which leads to increased bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, many data show the importance of IL-6 in the development of chronic inflammatory-associated diseases (particularly rheumatoid arthritis and inflammatory bowel disease) [23,24] as well as post-menopausal osteoporosis. In particular, it is well established that circulating levels of IL-6 display an age-associated increase [25]; moreover, both human and animal studies suggest that bone loss associated with the menopause may be linked to activation of osteoclasts by IL-6, as a consequence of the removal of the strong inhibitory activity of estrogens upon the production of this cytokine by osteoblasts [26].…”
Section: Discussionmentioning
confidence: 99%